Case Report: Exacerbation of varices following atezolizumab plus bevacizumab treatment of hepatocellular carcinoma: A case series and literature review - Suzuki, Hiroyuki; Iwamoto, Hideki; Shimose, Shigeo; Niizeki, Takashi; Shirono, Tomotake; Noda, Yu; Kamachi, Naoki; Yamaguchi, Taizo; Nakano, Masahito; Kuromatsu, Ryoko; Koga, Hironori; Kawaguchi, Takumi (Frontiers in Oncology, 2022)
Recently, a combined regimen of atezolizumab and bevacizumab (AB) treatment has been approved as a first-line treatment in patients with advanced hepatocellular carcinoma (HCC), contributing to prolonged survival. However, we often encounter cases where treatment must be discontinued due to the occurrence of adverse events. One of these events, which is often fatal, is gastrointestinal bleeding. To clarify the clinical effects of gastrointestinal bleeding after AB treatment, we evaluated patients with HCC who were treated with AB at our institution. Of the 105 patients, five treated with AB developed gastrointestinal bleeding, necessitating treatment discontinuation. Additionally, we encountered two cases where exacerbation of varicose veins was observed, and AB therapy could be continued by preventive treatment of varices. In conclusion, an appropriate follow-up is required during treatment with AB to prevent possible exacerbation of varicose veins.